Show Girls - Lam, Meilan (Office national du film du Canada, 1998)
Show Girls celebrates Montreal's swinging Black jazz scene from the 1920s to the 1960s, when the city was wide open. Three women who danced in the legendary Black clubs of the day - Rockhead's Paradise, The Terminal, Café St. Michel - share their unforgettable memories of life at the centre of one of the world's hottest jazz spots. From the Roaring Twenties, through the Second World War and on into the golden era of clubs in the fifties and sixities, Show Girls chronicles the lives of Bernice, Tina and Olga - mixing their memories with rarely seen footage of the era. Their stories are told against a backdrop of the fascinating social and political history that made Montreal a jazz and nightclub hotspot for decades. It is a story of song and dance, music and pride.

Haitian Popular Music in Montreal: The Effects of Acculturation - Juste-Constant, Voegeli; Shepherd, John (Popular Music, 1990)
Publisher: Cambridge University Press

Who's Who of Jazz in Montreal: Ragtime to 1970 - Gilmore, John (Véhicule Press, 1989)

Petite histoire des musiques afro-montréalaises - Villefranche, Robert; Bernard, Yves (MUSICultures, 1989)
Robert Villefranche and Yves Bernard describe the history of Montreal musicians of African descent, telling of the formation of various groups that performed at community events and festivals and became more widely known through recordings and festivals.

La musique populaire haïtienne à Montréal - Juste-Constant, Voegeli (Université de Montréal, 1985)

You Can Be Anything You Want: An Interview with Beverly Glenn-Copeland - Merril, Judith (Canadian Woman Studies, 1979)